Civic Education and the Prevention of Violent Extremism: Evidence from Indonesian Schools - Hardiansyah; Jihan Fauziah; Masnuripa Siregar; Sindy Syahputri (Yayasan Zia Salsabila, 2025)
The purpose of this study is to describe the Prevention of Terrorism and Radicalism in Indonesia in Schools. This study uses a qualitative approach with a literature study method by collecting relevant data and analyzing and studying it in detail and in depth, and conducting discussions to discuss the context related to the material in the journal. From this study, the results were found, namely (1) Radicalism in schools is caused by various structural and cultural factors, including past political pressure, repressive education, and minimal critical literacy. (2) Prevention efforts have been made by schools, the government, and the community, but are still sectoral and not optimally coordinated. (3) Social media has become a new channel for the spread of radical ideology, especially for students who are looking for their identity. As an implication of this research, it is understood that character education is not enough if it is not accompanied by strengthening digital literacy and active parental involvement. Then, in other aspects, teachers need continuous training to be able to recognize early symptoms of radicalism and respond in an educational and non-repressive manner. For that, policies are needed that are not only top-down, but also flexible to adjust to the socio-cultural characteristics of each region.